The Key Factors of Evaluating Agile Approaches: A Systematic Literature Review - Alaidaros, Hamzah; Omar, Mazni; Romli, Rohaida (ExcelingTech, 2019)
Currently, Agile Methods (AMs) are extensively being used in projects of various sizes and in different environments, thus surpassing their primary intended scope. For instance, they have been executed in distributed and non-distributed projects. In addition, AMs have been implemented in different project fields, such as engineering, medicine, banking, and manufacturing. Consequently, different Agile approaches have been proposed and integrated with other approaches in order to support the increased demand for diverse project environments. In this direction, various authors have examined the process of developing those approaches; however, the focus on explaining evaluation phases is scarce and scattered. Therefore, this study aims to review pertinent literature to identify the key factors and methodologies used to evaluate the proposed approaches in the Agile domain. The systematic literature review (SLR) methodology was adopted to identify, evaluate, and interpret all existing studies relevant to the research objective. SLR provides in-depth and more thorough results than an ordinary literature review. Forty-eight studies were selected and analyzed. The results show that applicability, effectiveness, and efficiency are the three most frequently examined evaluation factors, whereas case studies and surveys are the most frequently used research methods in evaluation studies. Factors identified in this review provide the evidence and the opportunity to design instruments or assessment forms that meet the needs of those researchers who are planning to evaluate their proposed Agile approaches.